2018
DOI: 10.1039/c8fo00688a
|View full text |Cite
|
Sign up to set email alerts
|

An integrated metabolomic strategy for the characterization of the effects of Chinese yam and its three active components on septic cardiomyopathy

Abstract: Chinese yam (CY), used as both a traditional Chinese medicine and a nutritious food, is an excellent candidate for treating septic cardiomyopathy (SCM). Adenosine, arbutin and allantoin are the major active components in the aqueous extract of CY. The aim of the present study was to interpret the roles of CY, adenosine, arbutin and allantoin in SCM treatment. Firstly, significant physiological indexes were examined to assess the model and treatment effects of CY, adenosine, arbutin and allantoin. Then, a metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Tryptophan is metabolized mainly by a rate-limiting enzyme, indoleamine 2,3-dioxygenase (IDO) through the kynurenine pathway (KP) ( Badawy, 2017 ). IDO can be driven by the gut microbiota and proinflammatory cytokines (e.g., interferon-γ, TNF-α, prostaglandin-E2 ( Li et al, 2020 ; Liu et al, 2021 ; Zhou, N. et al, 2018 ). In the present study, levels of tryptophan catabolites through the KP (e.g., kynurenic acid, xanthurenic acid) were increased in the model group, suggesting upregulated IDO activity, microbial dysbiosis and release of proinflammatory factors in PE.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is metabolized mainly by a rate-limiting enzyme, indoleamine 2,3-dioxygenase (IDO) through the kynurenine pathway (KP) ( Badawy, 2017 ). IDO can be driven by the gut microbiota and proinflammatory cytokines (e.g., interferon-γ, TNF-α, prostaglandin-E2 ( Li et al, 2020 ; Liu et al, 2021 ; Zhou, N. et al, 2018 ). In the present study, levels of tryptophan catabolites through the KP (e.g., kynurenic acid, xanthurenic acid) were increased in the model group, suggesting upregulated IDO activity, microbial dysbiosis and release of proinflammatory factors in PE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that continuous infusion of TNF-α interferes with the synthesis of cardiac proteins and eventually reduces the synthesis of myocardial fiber and sarcoplasmic proteins, which may be related to the effects of TNF-α on mRNA translation efficiency (28). In addition, an increasing number of studies have shown that pro-inflammatory factors and anti-inflammatory factors are involved in the progression of sepsis (29)(30)(31). When the dynamic balance of pro-inflammatory and anti-inflammatory reactions is disrupted, the body becomes injured (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still a major challenge to alleviate sepsis-induced myocardial injury. Moreover, some recent reports have shown that herbal medicines could improve cardiac function and reduce myocardial enzyme levels in septic cardiomyopathy [ 6 , 7 ]. Therefore, it urgently needs more effective drugs for protection against myocardial injury in septic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%